Silk-like FDY fiber and preparation method thereof
By adding modified zinc oxide whiskers in the preparation process of imitation silk FDY silk and adjusting the drafting conditions of the hot rolls, the problem of poor dyeing performance of imitation silk FDY silk is solved, and dyeing and production efficiency are improved.
Patent Information
- Application Number
- CN202510137754.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-02-07
AI Technical Summary
The dyeing performance of imitation silk FDY silk is not high, resulting in a low dyeing rate, increasing production costs, and may bring about environmental protection problems.
Modified zinc oxide whiskers are added to the polyester melt by an online addition system, and the hot roll temperature and drafting ratio are reduced during the hot roll drafting and shaping process, thereby improving the dyeing performance of the fibers.
It effectively improves the dyeing performance of the fiber, increases the dyeing degree, reduces the phenomenon of wool and broken heads, and improves production efficiency and product superiority.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of polyester spinning, and in particular to a silk-like FDY fiber and a preparation method thereof. Background Art
[0002] As a classic textile material, silk is widely used in high-end clothing, home furnishing, painting, embroidery and other industries with its unique advantages such as gorgeous luster, light texture, soft feel and strong comfort. However, the development of the silk industry faces many challenges. From the production perspective, the production process of silk is extremely complicated and cumbersome. From the cocoon breeding to the subsequent silk extraction, weaving, dyeing and other links, it not only requires a lot of manpower investment, but also has high technical requirements, which makes it difficult to improve production efficiency. At the same time, its raw material supply is restricted by the cocoon output, and the breeding process is easily affected by factors such as climate, pests and diseases, resulting in large fluctuations in the raw material market, further pushing up production costs, and ultimately causing silk prices to remain high. In addition, the output of silk cocoons is limited, with obvious seasonal and regional restrictions, and cannot meet large-scale market demand. The problem of low output is more prominent.
[0003] In order to meet the market demand for silk-like products and solve the many problems of silk, the manufacturing process of imitating silk with artificial fiber FDY silk came into being and gradually matured. This process mainly achieves the imitation silk effect through special-shaped cross-section or fine-denier silk. The special-shaped fiber imitates the triangular cross-section of silk, so that the fiber can refract and split light like a prism, thereby producing a silk-like luster. Fine-denier silk increases the layered structure of the silk in the product, strengthens the light reflection ability of the fiber inside, and makes the fiber fabric present a more delicate luster.
[0004] However, this silk-like technology also has certain limitations. The hue and depth of the fiber after dyeing depends on the surface reflected light and the refracted light generated inside the fiber. However, due to the large surface reflection of special-shaped cross-section silk and fine denier silk, the fiber color is lighter and the dyeing degree is lower when dyed with the same amount of dye. If you want to dye a dark color, you must increase the amount of dye, which not only increases production costs, but also may bring environmental problems. Summary of the invention
[0005] In order to solve the problem that the current imitation silk FDY silk has low dyeing performance and low dyeing rate, the present application provides a imitation silk FDY fiber and a preparation method thereof.
[0006] In the first aspect, the present application provides a method for preparing a silk-like FDY fiber, wherein 1 to 3 wt% of modified zinc oxide whiskers are added to a polyester melt through an online adding system, and then the melt is extruded from a spinning assembly to obtain a monofilament with a fineness of 0.5 to 1 dtex, and then the monofilament is cooled, oiled, pre-interwoven, hot roller drawing and shaping, main interwoven, and wound to obtain a silk-like FDY fiber; the aspect ratio of the aluminum oxide whiskers is 10 to 20; The hot roller stretching and shaping adopts five groups of hot rollers, namely HR1, HR2, HR3, HR4, and HR5. The temperature of HR1, HR2, and HR3 is 82±2°C, the temperature of HR4 and HR5 is 132±2°C, the stretching ratio between HR1 and HR2 is 1.01-1.06, the stretching ratio between HR2 and HR3 is 1.08-1.12, and the stretching ratio between HR3 and HR4 is 1.20-1.32.
[0007] In any of the above technical solutions, the rotational speeds of HR1, HR2, and HR3 are 3080±20m / min, 3130±20m / min, and 3630±20m / min, respectively, and the rotational speed of HR4 and HR5 is 4650±20m / min.
[0008] In any of the above technical solutions, the contact length between the fiber and the hot roller is 62 to 66% of the outer diameter of the hot roller.
[0009] After the hot rollers are drawn and fixed, the fiber orientation and crystallinity are high, and the macromolecules of the fiber are arranged in a relatively neat manner, which makes it difficult for the dye molecules to penetrate into the fiber, thus affecting the dyeing performance of the fiber. The present application effectively improves the fiber dyeing performance by reducing the temperature of the HR1, HR2 and HR3 hot rollers and the drafting multiples between the HR1, HR2, HR3 and HR4 rollers. Specifically, after the fiber is drawn by the HR1, HR2 and HR3 hot rollers, its orientation and crystallinity are low, and gaps and channels for the dye to penetrate are formed in the fiber, thereby improving the dyeing performance.
[0010] It should be noted that the temperature of the HR1, HR2 and HR3 hot rollers must be higher than the glass transition temperature, that is, above 68°C. On this basis, the lower the temperature, the more conducive it is to improving the dyeing performance. However, when the temperature is too low, the molecular chain segments are inactive, and the tow is prone to cold stretching, resulting in uneven elongation or hairy fibers. The speed of the HR1, HR2 and HR3 hot rollers should be low to improve the heating efficiency by reducing the speed. The function of the HR4 and HR5 hot rollers is to shape, and their temperature mainly affects the boiling water shrinkage of the fiber. In order to meet the boiling water shrinkage requirements of spun silk products, the above-mentioned shaping temperature is selected. The speed of the HR4 hot roller is basically the same as that of the HR5 hot roller, which mainly plays a role in stabilizing the tension balance between the two rollers, ensuring that the tow does not shake on the hot roller and increasing the shaping time.
[0011] The above-mentioned fiber is not drafted enough in the hot roller drawing process, which will cause the orientation degree and crystallinity to be low, and the breaking strength and elongation at break to decrease. In addition, since the imitation silk fiber has a larger specific surface area, the static electricity generated by the friction with the air is larger, which causes the fiber to easily shake on the hot roller during the drawing process, and the contact area between the filament bundle and the hot roller is inconsistent. The above phenomena have jointly caused the increase of fiber fuzziness and broken ends, affecting production efficiency and product quality rate. For this reason, the present application adds modified zinc oxide whiskers, which are dispersed in the fiber to inhibit the excessive close arrangement of molecular chains and form certain channels or gaps inside the fiber, making it easier for dye molecules to enter the fiber. At the same time, the whiskers can be arranged along the fiber extrusion direction, thereby improving the orientation degree of the fiber and compensating for the strength performance loss caused by its insufficient drafting. In addition, the addition of zinc oxide whiskers can alleviate the static electricity accumulation caused by friction, which is conducive to reducing the fiber fuzziness and broken ends.
[0012] In addition, it should be noted that a zinc oxide whisker with a large aspect ratio is prone to cause hairiness and broken ends; a small aspect ratio has little effect on improving the fiber dyeing performance. If conventional granular or spherical fillers such as calcium carbonate are added, it will not promote the improvement of fiber orientation. Instead, it will reduce the dye penetration channel in the fiber due to the strong induced crystallization effect, affecting the dyeing effect.
[0013] In any of the above technical schemes, the preparation method of the modified zinc oxide whisker is: zinc oxide whiskers and aminosilane coupling agent in a mass ratio of 100:3-6 are mixed in ethanol, and the amino whiskers are obtained by filtering, washing and drying; then the amino whiskers and terminal carboxyl hyperbranched polyester in a mass ratio of 100:5-10 are added to N,N-dimethylformamide, reacted at 100-120°C, filtered, washed and dried to obtain.
[0014] In any of the above technical solutions, the molecular weight of the carboxyl-terminated hyperbranched polyester is 1000-6000, and the carboxyl content (number of carboxyl groups) per unit molar mass of the carboxyl-terminated hyperbranched polyester is 6-24 mol.
[0015] In order to ensure the realization of the performance of zinc oxide whiskers, it is necessary to ensure that they are uniformly dispersed in the fiber. The present application improves the compatibility of the whiskers with polyester by grafting hyperbranched polyester on the whisker surface, so that the whiskers can be uniformly dispersed in the polyester matrix during melt blending. In addition, the terminal carboxyl groups in the carboxyl-terminated hyperbranched polyester can form a certain chemical connection with the carboxyl groups in the polyester melt, which helps to improve the strength performance of the fiber.
[0016] In any of the above technical solutions, a 400-mesh filter, 80-100-mesh glass beads, a 100-mesh filter, and 40-60-mesh glass beads are arranged in the sand cup of the spinning assembly from bottom to top, and the initial pressure of the spinning assembly is 17.9 MPa.
[0017] The filter component in the sand cup is used to filter impurities in the polyester melt. Conventional sand cups are mostly filled with metal sand for filtering. They have high profile, large specific surface area, and stronger filtering ability. However, the high profile of the metal sand causes large friction with the melt, resulting in a high temperature rise, and it is easy to pierce the melt, and cause zinc oxide whiskers with a relatively large length-to-diameter ratio to be separated from the melt and form agglomerates, which in turn causes fiber breakage. The present application uses glass microbeads as filter fillers, which can effectively filter and effectively prevent breakage caused by agglomeration of zinc oxide whiskers in the melt.
[0018] In any of the above technical solutions, the diameter of the aluminum oxide whisker is 1 to 2 microns and the length is 10 to 30 microns.
[0019] In any of the above technical solutions, the oiling uses an emulsion with an oil concentration of 95.5±0.3wt%, an oil temperature of 40±2°C, and the oil nozzle is a round hole oil nozzle with a diameter of 0.16±0.02mm.
[0020] In any of the above technical solutions, the pre-network air pressure is 0.1-0.2 MPa, and the main network air pressure is 0.2-0.4 MPa.
[0021] In any of the above technical solutions, the annular wind pressure during cooling is 16±2Pa, and the annular wind temperature is 20.5±1°C.
[0022] The silk-like FDY fiber has a large specific surface area and has a large friction with the yarn guide during the drawing process, which can easily cause a decrease in strength and cause white monomer coking on the yarn guide, affecting the uniformity of fiber dyeing and reducing the dyeing ability. After oiling, the present application uses the air pressure of the pre-network to homogenize the oil agent, eliminate static electricity, increase the smoothness of the yarn bundle, and allow the oil agent to penetrate into the interior of the yarn bundle, making the monofilaments more tightly bonded. The gaps between the monofilaments are filled with the oil agent. During the heating process of the hot roller, the oil agent has good thermal conductivity, which can make the monofilaments heated evenly and draw more evenly, thereby improving the uniformity of dyeing.
[0023] In addition, the oil temperature will affect the apparent viscosity of the oil. If the temperature is too low, the fluidity will be poor and the permeability will decrease. If the temperature is too high, the adhesion of the oil on the yarn bundle will decrease. Unstable oil temperature will cause uneven oiling of the yarn bundle. Through experiments, when the oil temperature is controlled at 40±2℃, the oil fluidity is optimal, the fiber oiling is more evenly applied, and the dyeing is optimal; using this temperature can achieve better permeability and adhesion.
[0024] In the second aspect, the present application provides a silk-like FDY fiber, which is produced by any of the above-mentioned methods; the fiber has a hairiness degradation rate of ≤2.7%, a dyeing degree ≥4 levels, a breaking strength ≥4.4cN / dtex, an elongation at break of 28±3%, a boiling water shrinkage of 6.5±0.5%, a dyeing rate ≥90%, and a K / S value ≥23.
[0025] In summary, this application has the following beneficial effects: By reducing the temperature of the hot roller and the drafting multiple, the problem of poor dyeing performance and low dyeing rate of the imitation silk FDY fiber is effectively solved. Furthermore, the modified zinc oxide whisker is blended with the polyester matrix to effectively compensate for the loss of fiber strength caused by insufficient drafting, while promoting the increase of dye penetration channels in the fiber, further improving the fiber dyeing degree. In addition, the present application optimizes the filtering structure of the sand cup in the spinning assembly based on the application of zinc oxide whiskers, reducing the phenomenon of broken ends of the hairy fibers. DETAILED DESCRIPTION Preparation Example
[0026] Preparation Example 1: A modified zinc oxide whisker is prepared by the following method: Take 100g of zinc oxide whiskers (length 15 microns, diameter 1 micron) and 5g of aminopropyltrimethoxysilane in ethanol, mix them, stir and react for 20 minutes, filter and separate the whiskers, wash the unreacted aminopropyltrimethoxysilane with ethanol, then put them in an oven and dry them at 50°C to obtain amino whiskers. Take 100g of amino whiskers and 7g of terminal carboxyl hyperbranched polyester (molecular weight 2800, number of carboxyl groups 12) and add them to N,N-dimethylformamide, react at 110°C for 4h, filter and separate the whiskers, wash them with N,N-dimethylformamide and water in turn, and put them in an oven to dry.
[0027] Preparation Example 2: A modified zinc oxide whisker is prepared by the following method: Take 100g of zinc oxide whiskers (length 10 microns, diameter 1 micron) and 3.3g of aminopropyltrimethoxysilane in ethanol, stir and react for 20 minutes, filter and separate the whiskers, wash the unreacted aminopropyltrimethoxysilane with ethanol, then put it in an oven and dry it at 50°C to obtain amino whiskers. Take 100g of amino whiskers and 5g of terminal carboxyl hyperbranched polyester (molecular weight 5700, number of carboxyl groups 24) and add them to N,N-dimethylformamide, react at 110°C for 4h, filter and separate the whiskers, wash them with N,N-dimethylformamide and water in turn, and put them in an oven to dry.
[0028] Preparation Example 3: A modified zinc oxide whisker is prepared by the following method: Take 100g of zinc oxide whiskers (length 20 microns, diameter 1 micron) and 6g of aminopropyl triethoxysilane, mix them in ethanol, stir and react for 20 minutes, filter and separate the whiskers, wash the unreacted aminopropyl triethoxysilane with ethanol, then put them in an oven and dry them at 50°C to obtain amino whiskers. Take 100g of amino whiskers and 10g of terminal carboxyl hyperbranched polyester (molecular weight 2600, number of carboxyl groups 12) and add them to N,N-dimethylformamide, react at 110°C for 4h, filter and separate the whiskers, wash them with N,N-dimethylformamide and water in turn, and put them in an oven to dry.
[0029] Preparation Example 4, a modified zinc oxide, is different from Preparation Example 1 in that the zinc oxide whiskers (length 20 μm, diameter 1 μm) are replaced with an equal amount of zinc oxide whiskers (length 30 μm, diameter 1 μm).
[0030] Preparation Example 5: A modified zinc oxide whisker is prepared by the following method: Take 100g of zinc oxide whiskers (length 15 microns, diameter 1 micron) and mix them with 5g of aminopropyltrimethoxysilane in ethanol, stir and react for 20 minutes, filter and separate the whiskers, wash the unreacted aminopropyltrimethoxysilane with ethanol, and then put it into an oven and dry it at 50°C.
[0031] Preparation Example 6, a modified zinc oxide, is different from Preparation Example 1 in that the zinc oxide whiskers (length 20 microns, diameter 1 micron) are replaced with an equal amount of zinc oxide powder with an average particle size of 200 nm.
[0032] Preparation Example 7, a modified calcium carbonate whisker, is different from Preparation Example 1 in that the zinc oxide whisker (length 20 μm, diameter 1 μm) is replaced by an equal amount of calcium carbonate whiskers (length 20 μm, diameter 1 μm). Example
[0033] Raw material selection in the embodiment: the intrinsic viscosity of polyester chips is 0.632±0.006dL / g, and the terminal carboxyl value is 46±3mol / t.
[0034] Embodiment 1, a kind of imitation silk fiber, preparation method is as follows: 1.5 kg of modified zinc oxide whiskers were added into 98.5 kg of polyester melt through an online adding system. The polyester melt was then filtered through the sand cup of the spinning assembly and extruded from the spinneret to obtain a monofilament with a fineness of 0.56 dtex. The monofilament was subjected to ring-blown cooling, oil bundling, pre-networking, hot roller drawing and shaping, main networking, and winding to obtain 40 dtex / 72F silk-like FDY fiber.
[0035] Among them, the sand cup is filled with a 400-mesh filter, 60 g of 80-100-mesh glass beads, a 100-mesh filter, and 40 g of 40-60-mesh glass beads from bottom to top, and the initial pressure of the spinning assembly is 17.9 MPa.
[0036] Among them, the annular blowing air pressure is 16±2pa, the annular blowing air temperature is 20.5±1℃; the oiling adopts an emulsion with an oil concentration of 95.5wt%, the oil temperature is 40℃, and the oil nozzle adopts OJ160 with a round hole oil nozzle, and its diameter is 0.16±0.02mm. The pre-network air pressure is 0.12MPa, and the main network air pressure is 0.26MPa.
[0037] Among them, the hot roller stretching and shaping adopts a five-roller stretching and shaping equipment, which has five rollers including HR1, HR2, HR3, HR4, and HR5 hot rollers arranged in sequence. The temperature of the HR1, HR2, and HR3 hot rollers is 82°C, and the temperature of the HR4 and HR5 hot rollers is 132°C. The rotation speeds of HR1, HR2, HR3, HR4, and HR5 are 3080m / min, 3130m / min, 3630m / min, 4650m / min, and 4650m / min, respectively; the contact length between the fiber and the hot roller is 63-64% of the outer diameter of the corresponding hot roller, respectively; the stretching ratio between HR1 and HR2 is 1.04, the stretching ratio between HR2 and HR3 is 1.10, and the stretching ratio between HR3 and HR4 is 1.28.
[0038] Embodiment 2, a kind of imitation silk fiber, preparation method is as follows: Through the online adding system, 2.6 kg of modified zinc oxide whiskers were added into 97.4 kg of polyester melt. The polyester melt was then filtered through the sand cup of the spinning assembly and extruded from the spinneret to obtain a monofilament with a fineness of 0.56 dtex. The monofilament was subjected to ring-blown cooling, oil bundling, pre-networking, hot roller drawing and shaping, main networking and winding to obtain 40 dtex / 72F silk-like FDY fiber.
[0039] Among them, the sand cup is filled with a 400-mesh filter, 60 g of 80-100-mesh glass beads, a 100-mesh filter, and 40 g of 40-60-mesh glass beads from bottom to top, and the initial pressure of the spinning assembly is 17.9 MPa.
[0040] Among them, the annular blowing air pressure is 16±2pa, the annular blowing air temperature is 20.5±1℃; the oiling adopts an emulsion with an oil concentration of 95.5wt%, the oil temperature is 42℃, and the oil nozzle adopts OJ160 with a round hole oil nozzle, and its diameter is 0.16±0.02mm. The pre-network air pressure is 0.15MPa, and the main network air pressure is 0.35MPa.
[0041] Among them, the hot roller stretching and shaping adopts a five-roller stretching and shaping equipment, which has five rollers including HR1, HR2, HR3, HR4, and HR5 hot rollers arranged in sequence. The temperature of the HR1, HR2, and HR3 hot rollers is 82°C, and the temperature of the HR4 and HR5 hot rollers is 132°C. The rotation speeds of HR1, HR2, HR3, HR4, and HR5 are 3070m / min, 3130m / min, 3620m / min, 4665m / min, and 4665m / min respectively; the contact length between the fiber and the hot roller is 63-64% of the outer diameter of the hot roller respectively; the stretching ratio between HR1 and HR2 is 1.05, the stretching ratio between HR2 and HR3 is 1.09, and the stretching ratio between HR3 and HR4 is 1.31.
[0042] Example 3, a silk-like fiber, is different from Example 1 in that the modified zinc oxide whiskers of Preparation Example 1 are replaced by an equal amount of the modified zinc oxide whiskers of Preparation Example 3.
[0043] Example 4, a silk-like fiber, is different from Example 1 in that the modified zinc oxide whiskers of Preparation Example 1 are replaced by an equal amount of the modified zinc oxide whiskers of Preparation Example 4.
[0044] Example 5, a silk-like fiber, is different from Example 1 in that the modified zinc oxide whiskers of Preparation Example 1 are replaced by an equal amount of the modified zinc oxide whiskers of Preparation Example 5.
[0045] Example 6, a silk-like fiber, differs from Example 1 in that the glass beads in the sand cup are replaced with metal sand in equal amounts. Comparative Example
[0046] Comparative Example 1 is a silk-like fiber, which differs from Example 6 in that the modified zinc oxide whiskers of Preparation Example 1 are replaced by an equal amount of the modified zinc oxide of Preparation Example 6.
[0047] Comparative Example 2 is a silk-like fiber, which differs from Example 6 in that the modified zinc oxide whiskers of Preparation Example 1 are replaced by an equal amount of modified calcium carbonate whiskers of Preparation Example 7.
[0048] Comparative Example 3 is a silk-like fiber, which is different from Example 6 in that no modified zinc oxide whiskers are added to the polyester melt.
[0049] Comparative Example 4 is a silk-like fiber, which is different from Comparative Example 3 in that the drafting ratio between HR1 and HR2 is 1.12, the drafting ratio between HR2 and HR3 is 1.25, and the drafting ratio between HR3 and HR4 is 1.43. Performance testing
[0050] 1. With reference to GB / T 6508-2015 "Test method for dyeing uniformity of polyester filament", the silk-like FDY fibers obtained in the embodiment and the comparative example were woven into socks and dyed respectively, and then the dye uptake of the socks was measured by a spectrophotometer, and the K / S value of the socks was determined by a colorimeter.
[0051] 2. Refer to FZ / T 54039-2018 "Special-shaped polyester drawn yarn" to determine the fiber dyeing uniformity, breaking strength, breaking elongation and boiling water shrinkage.
[0052] 3. Downgrading rate of rough silk: rough silk will be downgraded if there are more than 2 single-filament breakage defects on the surface of each silk roll. Each silk roll weighs 8kg. Downgrading rate of rough silk = number of downgraded rough silk × 100% / total number of silk.
[0053] 4. Excellent rate = {total number of pieces - (number of broken ends and small curls + number of downgraded wool silk pieces + number of downgraded dyeing pieces + number of other downgraded pieces)} × 100% / total number of pieces.
[0054] Table 1. Performance test results
[0055] Combining Example 1, Comparative Example 3 and Table 1, it can be seen that adding modified zinc oxide whiskers in the preparation of FDY fibers significantly improves the dyeing properties such as dye uptake, K / S value and strength properties such as breaking strength of the fibers. In addition, the FDY fibers prepared using non-whisker structure zinc oxide powder (Comparative Example 1) perform poorly in dyeing properties such as dye uptake and K / S value compared to the FDY fibers prepared using modified zinc oxide whiskers. The reason may be that zinc oxide whiskers can promote the formation of dye penetration channels in polyester, while zinc oxide powder has a significant effect on promoting the formation of crystalline regions, which can improve fiber strength but reduce dye penetration channels, which is not conducive to improving dyeing properties. FDY fibers prepared using calcium carbonate whiskers (Comparative Example 2) are prone to forming hairy fibers during manufacturing, which reduces the product quality rate. The reason may be that calcium carbonate is not conducive to improving the antistatic properties of fibers compared to zinc oxide. For silk-like FDY fibers with a small fineness and a large specific surface area, static electricity is easily generated during the spinning process, forming hairy fibers.
[0056] Combining Example 4 and Table 1, it can be seen that if the aspect ratio of the zinc oxide whisker is too long, the fiber fuzziness and broken ends will increase, and the product quality rate will decrease. Combining Example 5 and Table 1, it can be seen that only aminosilane coupling agent is used to modify the zinc oxide whisker, and the resulting fiber has poor strength performance. Combining Example 6 and Table 1, it can be seen that compared with glass bead filtration, the FDY fiber obtained by metal sand filtration is prone to fuzziness and broken ends, and the product quality rate is reduced.
[0057] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing silk-like FDY fiber, characterized in that: 1-3 wt% of modified zinc oxide whiskers are added to a polyester melt through an online adding system, and then the melt is extruded from a spinning assembly to obtain a monofilament with a fineness of 0.5-1 dtex, which is then subjected to cooling, oiling, pre-internetting, hot roller drawing and shaping, main internetting, and winding to obtain a silk-like FDY fiber; the aspect ratio of the aluminum oxide whiskers is 10-20; The hot roller stretching and shaping adopts five groups of hot rollers, namely HR1, HR2, HR3, HR4, and HR5. The temperature of HR1, HR2, and HR3 is 82±2°C, the temperature of HR4 and HR5 is 132±2°C, the stretching ratio between HR1 and HR2 is 1.01-1.06, the stretching ratio between HR2 and HR3 is 1.08-1.12, and the stretching ratio between HR3 and HR4 is 1.20-1.
32.
2. The preparation method according to claim 1, characterized in that: The rotation speeds of HR1, HR2 and HR3 are 3080±20m / min, 3130±20m / min and 3630±20m / min respectively, and the rotation speed of HR4 and HR5 is 4650±20m / min; and / or the contact length between the fiber and the hot roller is 62-66% of the outer diameter of the hot roller.
3. The preparation method according to claim 1, characterized in that: The modified zinc oxide whisker preparation method comprises the following steps: mixing zinc oxide whiskers and aminosilane coupling agent in a mass ratio of 100:3-6 in ethanol, filtering, washing and drying to obtain amino whiskers; then adding amino whiskers and carboxyl-terminated hyperbranched polyester in a mass ratio of 100:5-10 into N,N-dimethylformamide, reacting at 100-120°C, filtering, washing and drying to obtain the modified zinc oxide whisker.
4. The preparation method according to claim 1, characterized in that: The molecular weight of the carboxyl-terminated hyperbranched polyester is 1000-6000, and the carboxyl content per unit molar mass of the carboxyl-terminated hyperbranched polyester is 6-24 moles.
5. The preparation method according to claim 1, characterized in that: The sand cup of the spinning assembly is provided with a 400-mesh filter, 80-100-mesh glass beads, a 100-mesh filter, and 40-60-mesh glass beads from bottom to top, and the initial pressure of the spinning assembly is 17.9 MPa.
6. The preparation method according to claim 1, characterized in that: The diameter of the aluminum oxide whisker is 1 to 2 microns, and the length is 10 to 30 microns.
7. The preparation method according to claim 1, characterized in that: The oiling is carried out using an emulsion with an oil concentration of 95.5±0.3wt%, an oil temperature of 40±2°C, and a round hole oil nozzle with a diameter of 0.16±0.02mm.
8. The preparation method according to claim 1, characterized in that: The pre-network air pressure is 0.1-0.2 MPa, and the main network air pressure is 0.2-0.4 MPa.
9. The preparation method according to claim 1, characterized in that: The annular air pressure during the cooling is 16±2Pa, and the annular air temperature is 20.5±1°C.
10. A silk-like FDY fiber, characterized in that: The fiber is prepared by the preparation method described in any one of claims 1 to 9; the fiber has a hair degradation rate of ≤2.7%, dyeing uniformity ≥4 levels, breaking strength ≥4.4cN / dtex, breaking elongation 28±3%, boiling water shrinkage 6.5±0.5%, dye uptake ≥90%, and K / S value ≥23.
Citation Information
Patent Citations
Production method of low-temperature easy-to-dye polyester fiber
CN102443871A
Manufacturing method of antibacterial deodorizing polyester fiber
CN102965760A
Preparation method of flame-retardant droplet-resistant terylene
CN102978735A
Method for manufacturing various-modulus flame-retardant anti-molten-drop polyester fibers
CN102978743A
Processing method of PBT (polybutylene terephthalate) polyester fiber for woolen sweaters
CN111893587A
Cited By
Polyester fiber for light-transmitting phantom yarn and preparation method of polyester fiber
CN120758999A